1. Not finding help here? Sign up for a free 30min tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Wave Equation for Second Sound in Superfluid He-4

  1. May 13, 2009 #1
    I am trying to derive the wave equation for 'Second Sound in superfluid Helium-4 using the basic tenets of the two-fluid model. I am following the derivation in a book which has intermediate steps along the way - I am trying to fill in the gaps. I am almost there - there is only one step that I cannot do:

    I cannot get from:

    (dVn/dt) - (dVs/dt) = (-p/pn).S.grad(T) ........... (1)

    to

    (pn/ps).d/dt(p.Div(Vn)) = -p.S.Laplacian(T) ........... (2)

    where S = entropy, T = temperature, ps = density of superfluid component, pn = density of normal component, p = pn + ps = overall density of helium, Div = divergence operation, grad = grad operation, Laplacian = Laplacian operator = div(grad(_)), Vn = velocity of normal component of Helium, Vs = velocity of superfluid component of Helium.

    The book says to take the divergence (Del) of both sides of eqn 1, and then use eqn 3 below to 'replace the superfluid velocity in the result', where upon eqn 2 apparently pops out after a little wrangling.

    Div(j) = -(dp/dt) ........... (3)

    Where j = pnVn + psVs ...........(4)


    It doesn't happen for me though!

    Setting dp/dt = 0 (a fair approximation in this case) in (3) and subbing in (4), I get:

    Div(Vs) = -(pn/ps).Div(Vn) ..........(5)

    Subbing (5) into (1) after taking the Div of both sides, I get:

    d/dt[Div(Vn) + (pn/ps).Div(Vn)] = -(p/pn).S.Laplacian(T) ............... (6)

    I can't work out how to go further or whether I've committed some mathematical howler! I need to get (6) to look like (2), unless I've stuffed up in arriving at (6)...

    Any help would be much appreciated!
     
  2. jcsd
  3. May 13, 2009 #2

    gabbagabbahey

    User Avatar
    Homework Helper
    Gold Member

    You're almost there;

    [tex]\vec{\nabla}\cdot\vec{v}_n+\left(\frac{p_n}{p_s}\right)\vec{\nabla}\cdot\vec{v}_n=\left(1+\frac{p_n}{p_s}\right)\vec{\nabla}\cdot\vec{v}_n[/tex]

    And

    [tex]1+\frac{p_n}{p_s}=\frac{p_s+p_n}{p_s}=\frac{p}{p_s}[/tex]
     
  4. May 13, 2009 #3
    Champion - I appreciate it a great deal - that has been driving me bloody well nuts!
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook




Similar Discussions: Wave Equation for Second Sound in Superfluid He-4
Loading...